2016
DOI: 10.1002/14651858.cd005092.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Cup feeding versus other forms of supplemental enteral feeding for newborn infants unable to fully breastfeed

Abstract: Cup feeding versus other forms of supplemental enteral feeding for newborn infants unable to fully breastfeed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 27 publications
3
33
0
5
Order By: Relevance
“…However, receiving human milk by cup or spoon is not a widespread practice worldwide, as well as in Brazil. Only a very small percentage of children receive human milk by spoon or cup, especially children of HIV positive women and extremely underweight children who are fed human milk from human milk bank, but only for a short period of time in their lives [45]. Furthermore, a randomized clinical trial analyzing associations between cup feeding, pacifier or bottle-feeding use and breastfeeding showed that supplementary feedings, regardless of the method (cup or bottle) used, have a detrimental effect on breast-feeding duration.…”
Section: Discussionmentioning
confidence: 99%
“…However, receiving human milk by cup or spoon is not a widespread practice worldwide, as well as in Brazil. Only a very small percentage of children receive human milk by spoon or cup, especially children of HIV positive women and extremely underweight children who are fed human milk from human milk bank, but only for a short period of time in their lives [45]. Furthermore, a randomized clinical trial analyzing associations between cup feeding, pacifier or bottle-feeding use and breastfeeding showed that supplementary feedings, regardless of the method (cup or bottle) used, have a detrimental effect on breast-feeding duration.…”
Section: Discussionmentioning
confidence: 99%
“…Anne, tüm oral beslenmeler için yenidoğan yoğun bakım üni-tesine gelemediğinde ya da preterm bebek çeşitli nedenlerle oral yolla beslenemediğinde annenin göğsünden emerek beslenene kadar alternatif beslenme yöntemlerine gereksinim duymaktadır. 9,10 DSÖ ve Bebek Dostu Hastaneler Programı'nda emzirilemeyen preterm bebeklerin fincanla veya kaşıkla beslenmesi gerektiği belirtilmektedir. Bu önerinin nedeni, biberonla beslemenin bebekte meme başı şaşkınlığı yaratarak daha sonra emzirmeye geçiş sürecini zorlaştırmasıdır.…”
Section: Preterm Bebeklerde Oral Beslenmeyeunclassified
“…10 Collins ve ark., fincanla beslenmenin biberonla beslenmeye göre daha uzun sürdüğünü, annelerin ve sağlık personelinin bu yöntemi kullanmak konusunda kendilerine güvenmediklerini, yöntemden memnun olmadık-larını ve kültürel olarak aşina oldukları ve daha iyi bildikleri biberonla beslemeyi tercih ettiklerini belirtirken, Aloysius ve Hickson, fincanla beslenme sırasında bebeklerin daha fazla stres belirtileri gös-terdiklerini ifade etmektedirler. 8,12 Literatürde biberonla ya da fincanla beslemenin avantaj ve dezavantajlarına ilişkin belirtilen farklı görüşler olmakla birlikte en sık tercih edilen ve güvenilir olan yöntemin biberonla besleme olduğu, bu yöntemin sağlık personeli ve anneler tarafından kullanılmaya devam edildiği bildirilmektedir.…”
Section: Preterm Bebeklerde Oral Beslenmeyeunclassified
See 1 more Smart Citation
“…However, a Cochrane review [11] concluded that, as a supplement to breastfeeding, cup feeding could not be recommended over bottle feeding because it had no significant benefit in maintaining breastfeeding beyond hospital discharge. Additionally, the review suggested that cup feeding had the potential to unacceptably lengthen the hospital stay.…”
Section: Introductionmentioning
confidence: 99%